The Business Practices of After the Second-Hand Clothes Import Ban in Indonesia (Studies at Jamblang and Nangka Traditional Market) - Ivandra, Verren; Basuki, Rizqy Aziz (Commercium : Journal of Business and Management, 2024)
This research project examines the experiences and performance of two small and medium-sized enterprises (SMEs) in the imported second-hand clothes industry following the implementation of Regulation of the Minister of Trade of the Republic of Indonesia No. 40 of 2022. The study involves two distinct sellers, one from the Jamblang Traditional Market and the other from the Nangka Traditional Market. The performance is assessed according to five dimensions: sales revenue, profit rate, distribution process, consumer traffic, and unexpected impacts. The qualitative method was utilized as the approach in this research. Data were collected through observation, interviews, and document analysis, and were subsequently analyzed using NVIVO 12. The findings of this research indicate that the implementation of the import ban on used clothes has a negligible impact on the performance of the two small retailers under study. The impact is initially experienced by the retailers, but as time progresses, the regulation is no longer perceived as a threat.